1974
DOI: 10.1099/00221287-83-1-63
|View full text |Cite
|
Sign up to set email alerts
|

Events Surrounding the Early Development of Euglena Chloroplasts: I Cellular Origins of Chloroplast Enzymes in Euglena*

Abstract: S U M M A R YDuring chloroplast development, the large increases in ribulose diphosphate carboxylase (RUDPCase) activity and cytochrome 5 5 2 concentration follow the pattern of chlorophyll synthesis, in that the formation of these two enzymes is inhibited by streptomycin (Sm) and by chloramphenicol (Cm) beyond 12 h of development. Neither enzyme can be detected in W,BUL, a mutant of Euglena in which chloroplasts and chloroplast DNA are undetectable. In contrast, the NADP-linked triose phosphate dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
22
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 32 publications
7
22
1
Order By: Relevance
“…Strep fomycin and plus f ids in resf ing Euglenu 61 development of the photosynthetic apparatus that we have measured are not affected by streptomycin, but some are strongly inhibited thereafter (Bovarnick et al 1974). This has been confirmed by us with fluorescence microscopy, and by electron microscopy (BenShaul, Silman & Ophir, 1972) where the structure of the developing plastid after 72 h in the presence of streptomycin resembles the normal plastid at 12 to 14 h development.…”
supporting
confidence: 65%
“…Strep fomycin and plus f ids in resf ing Euglenu 61 development of the photosynthetic apparatus that we have measured are not affected by streptomycin, but some are strongly inhibited thereafter (Bovarnick et al 1974). This has been confirmed by us with fluorescence microscopy, and by electron microscopy (BenShaul, Silman & Ophir, 1972) where the structure of the developing plastid after 72 h in the presence of streptomycin resembles the normal plastid at 12 to 14 h development.…”
supporting
confidence: 65%
“…The 24-h lag period for the photoinduction of glycolate dehydrogenase in resting Euglena (Fig. 4) differs from the lag periods (0-12 h) previously reported for other light-induced enzymes (3,14,15). In resting cells, glycolate dehydrogenase synthesis appears to begin only after the cells become photosynthetically competent (27) supporting Merrett's proposal (20) that glycolate dehydrogenase synthesis is controlled by a product of photosynthesis rather than directly by light exposure.…”
Section: Methodscontrasting
confidence: 48%
“…Do, a measure of sensitivity of the UV targets (17), was 4.5 sec for the wild type organism and 3.5 sec for Y9 cells. Exposure of (4,5,11,24,26) we observed the gradual appearance of these enzyme activities in dark-grown wild type cells exposed to light. The time course for the appearance of these activities over a 48-to 72-hr period and the finding that cycloheximide (15 ,g/ml) inhibited 80 to 95% of the light-induced formation of each of the four proteins strongly support the notion that each enzyme is synthesized de novo during chloroplast development in Euglena.…”
Section: Resultsmentioning
confidence: 85%
“…The kinetics of light-induced synthesis of NADP glyceraldehyde-3-P dehydrogenase in regreening cells of Euglena has been measured by several investigators (3,4,11,26). Brawerman and Konigsberg (5) advanced the hypothesis that photosynthetically generated NADPH might serve as an inducer of this enzyme in Euglena, and more recently Ben-Amotz and Avron (2) demonstrated that disalicylidenepropanediamine (DSPD), a potent antagonist of ferredoxin, prevented the light-induced formation of NADPH glyceraldehyde-3-P dehydrogenase in Euglena.…”
Section: Resultsmentioning
confidence: 99%